PELAKSANAAN TUGAS TELEPHONE OPERATOR DI HARRIS RESORT BARELANG BATAM - Esrawati, Lidya; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Batam city is one of the cities that has a variety of interisting natural tourism potential. To support the development of tourism pontential. To support the development of tourism, the industry in terms of accomodation is increasingly important, but only professional players can compete, namely HARRIS Resort Barelang Batam. To improve the image of this resort, each department must have a perfect form of service. The first impression obtained by guests comes from the front office department, one of which is the telephone operator section which is a "Guest Service Ambassador" in charge of providing telecommunication services in the form of overall information from a hotel's products, where direct telephone receivers, to telephone connections to receive guest requests. By having an important role in operations, as a telephone officer, operators are required to be able to multitask, skils, and understand all existing tasks and be able to override all obstacle factors that will hamper operations. Of course, in reducing complaints from guests against the services provided, telephone operators must carry out their duties in accordance with the directions and regulations in carrying out these duties called standard operating procedures. Therefore, to improve the quality of service provided by telephone operators, each officer must comply with standard operating procedures that are used as a reference in carrying out their duties as a good communication service center. The purpose of the standard operating procedure in carrying out the duties of this telephone operator is to provide satisfaction to guests for the service provided. Therefore, telephone operators must carry out the overall task as well as possible in order to improve the positive image of HARRIS Resort Barelang Batam. Keywords : Main task, Telephone Operator, SOP, HARRIS Resort Barelang Batam